(untitled) (Tempo e Argumento, 2021)
This article analyzes a magazine of the new Argentine left: Peronist Militancy for Liberation (1973-74). The publication is expressive of a specific current within revolutionary Peronism: "alternativeism" that, compared to other actors, has been little studied. It also expresses the process of identity transformation for the political group that emerged around the publication, making visible a particular path of political radicalization: the "leftization" of Peronism. Here we concentrate on the analysis of the Controversial Section, which represents an epistolary exchange between worker and Peronist characters. Unlike the rest of the periodical notes of the magazine, the Controversy Section represented a specific “reading contract”, with its own logic and the construction of multiple readers. As we will see, the section is a prism from which it is possible to show that process of identity transformation and the meanings of a disputed Peronism, reconstructing the stakes of the political group and the debates with the internal sectors of the Peronist movement, Perón and, also, with the movement organizations of revolutionary Peronism. Keywords: political identity; controversial section; Perón; alternativism; movementism.